2016
DOI: 10.3906/sag-1504-35
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mixed astigmatism: early clinical outcomes withWaveLight and Technolas excimer lasers

Abstract: There were no significant differences in refraction and visual acuity between the WaveLight and Technolas groups during a 3-month follow-up period after laser in situ keratomileusis for mixed astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…There was high treatment safety as no patient lost two or more lines of CDVA, which is consistent with many of the previous studies [8,[12][13][14][15][16][17][18][19][20][21]. At 12 months postoperatively, 80.8% of patients had a refractive cylinder no greater than 0.50 D and 100% had cylinders no greater [15,19,21,22], but only one study reported fewer than 60% of patients having a refractive cylinder no greater than 1.00 D [19]. Our results suggest that our findings are consistent with previous studies and showed improvement on other variables such as the mean reduction in refractive cylinder.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was high treatment safety as no patient lost two or more lines of CDVA, which is consistent with many of the previous studies [8,[12][13][14][15][16][17][18][19][20][21]. At 12 months postoperatively, 80.8% of patients had a refractive cylinder no greater than 0.50 D and 100% had cylinders no greater [15,19,21,22], but only one study reported fewer than 60% of patients having a refractive cylinder no greater than 1.00 D [19]. Our results suggest that our findings are consistent with previous studies and showed improvement on other variables such as the mean reduction in refractive cylinder.…”
Section: Discussionsupporting
confidence: 89%
“…The study demonstrated that by 12 months, 88% of patients had an SEQ no greater than 0.50 D of their intended SEQ target. There was high treatment safety as no patient lost two or more lines of CDVA, which is consistent with many of the previous studies [8,[12][13][14][15][16][17][18][19][20][21]. At 12 months postoperatively, 80.8% of patients had a refractive cylinder no greater than 0.50 D and 100% had cylinders no greater [15,19,21,22], but only one study reported fewer than 60% of patients having a refractive cylinder no greater than 1.00 D [19].…”
Section: Discussionsupporting
confidence: 86%